Sitting in Silence: Managing Aural Body Rhetoric in Public Restrooms. Issue 2 (14th March 2016) - Booth, E. Tristan; Spencer, Leland G.
Abstract : Proposing an enhancement to the concepts of verbal and corporeal rhetorics, this article offers the concept of aural body rhetoric, arguing that nonvocal sounds produced by the body can also provide rhetorical messages, create rhetorical challenges and prompt the conscious management of bodily sounds, particularly in panopticonic spaces (panauricons) in which the body is hidden from view. Using the urinary sounds made by transsexual men in public restrooms as an example, this article examines this space as a panauricon that creates a rhetorical challenge for these men and has prompted the dissemination of various rhetorical strategies within the community of transmen in the United States.